2017
DOI: 10.7717/peerj.3467
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of widely consumed herbal teas, alone or in combination with antibiotics: anin vitrostudy

Abstract: BackgroundBecause of increasing antibiotic resistance, herbal teas are the most popular natural alternatives for the treatment of infectious diseases, and are currently gaining more importance. We examined the antimicrobial activities of 31 herbal teas both alone and in combination with antibiotics or antifungals against some standard and clinical isolates of Pseudomonas aeruginosa, Acinetobacter baumannii, Escherichia coli, Klebsiella pneumoniae, Enterococcus faecalis, methicillin susceptible/resistant Staphy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Understanding the mechanisms involved in the anti-viral and anti-infectious activity of biochemical compounds require extensive in vivo testing in order to prove their efficiency in reducing the clinical signs of disease without a negative impact on animal health. We hypothesized that given the fact that in combination natural antimicrobials can act antagonistically against each other 18 a detailed scientific report is often required, allowing the end user to design informed interventions at farm level. In the present study we examined the in vitro activity of a mixture of citrus extract, maltodextrin, sodium chloride, lactic acid and citric acid (AuraShield L) against viruses causing infectious bronchitis (B1648), Newcastle disease (ATCC, 699), avian influenza (H9N2, ATCC, VR-1642), porcine reproductive and respiratory syndrome (ATCC, VR-2386) and bovine coronavirus (ATCC, VR-874).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms involved in the anti-viral and anti-infectious activity of biochemical compounds require extensive in vivo testing in order to prove their efficiency in reducing the clinical signs of disease without a negative impact on animal health. We hypothesized that given the fact that in combination natural antimicrobials can act antagonistically against each other 18 a detailed scientific report is often required, allowing the end user to design informed interventions at farm level. In the present study we examined the in vitro activity of a mixture of citrus extract, maltodextrin, sodium chloride, lactic acid and citric acid (AuraShield L) against viruses causing infectious bronchitis (B1648), Newcastle disease (ATCC, 699), avian influenza (H9N2, ATCC, VR-1642), porcine reproductive and respiratory syndrome (ATCC, VR-2386) and bovine coronavirus (ATCC, VR-874).…”
Section: Introductionmentioning
confidence: 99%
“…Markov et al, (2009) as extracts from dill seeds shows higher antimicrobial activity on E. coli compared to amoxicillin antibiotics and this contrast with Ljiljana P. et al, (2016) which reported that dill effect was observed the highest effect on Gram-positive m.o. On the other hand in this study, doxycycline antibiotic and Mint combinations may be recommended for E.coli infections, Similarly, Tuysuz et al, (2017) examined the antimicrobial activities of 31 different herbal teas for examples (Mint) both alone and in combination with antibiotics while Lee et al, (2005), also showed that Mint and ciprofloxacin combinations were synergistic against E. coli.…”
Section: Discussionmentioning
confidence: 93%
“…Tea polyphenols, as a natural extract of tea, have been shown to exert an inhibitory effect on the growth of fungi 7,22) . It has been reported that tea catechins demonstrate antibacterial activity against various pathogenic bacteria, as well 8,9) . The results of the present study showed that polyphenols were present in the tea extract, and that the higher the concentration, the higher the amount of polyphenols, that is to say, amount was concentration-dependent.…”
Section: Discussionmentioning
confidence: 99%